1992
DOI: 10.1093/jaoac/75.3.577
|View full text |Cite
|
Sign up to set email alerts
|

An FDA Laboratory Approach to Uncovering Potential Fraud in the Generic Drug Industry

Abstract: The Division of Drug Analysis of the U.S. Food and Drug Administration In St. Louis, MO, has screened more than 1400 drug samples for potential generic drug fraud by a combination of physical, instrumental, and chemical techniques. The approach to fraud centered around the analysis of exciplents as opposed to the normal approach of analysis of active Ingredients. Approximately 80% of the drug formulation pairs (Innovator and generic) submitted for bloequlvalence testing could be differentiated by a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In eqn (7), the matrix E i_winsize denotes the part of original residuals E inside the i th narrow window, P i_winsize contains the parts of the PCs inside the same window, I is a unit matrix of size (winsize 6 winsize), D i_winsize is the recalculated residuals corresponding to the residuals E i_winsize after compensation for the systematic fit errors. Compared with sPCR, this modified algorithm is friendly to use, and the results are more reasonable.…”
Section: Modification Of Secured Principal Component Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eqn (7), the matrix E i_winsize denotes the part of original residuals E inside the i th narrow window, P i_winsize contains the parts of the PCs inside the same window, I is a unit matrix of size (winsize 6 winsize), D i_winsize is the recalculated residuals corresponding to the residuals E i_winsize after compensation for the systematic fit errors. Compared with sPCR, this modified algorithm is friendly to use, and the results are more reasonable.…”
Section: Modification Of Secured Principal Component Regressionmentioning
confidence: 99%
“…5 Chromatography fingerprinting emphasizes an integral formulation of pharmacologically active and phytopharmaceutically characteristic components of samples with similar or different attributions. [6][7][8][9][10][11] The quality consistency and stability of herbal extracts or products can be assessed by their integral fingerprint patterns in quantified operation procedures. Therefore, it was formally introduced by WHO in Munich in 1991, 12 and subsequently accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these challenges, process patents have been difficult to defend. Common strategies to prosecute infringement involve evidence of organic impurities and/or trace metals that are argued to be foreign to the established manufacturing process. , These cases can be challenging due to ambiguities in the interpretation of what constitutes a trace impurity . In contrast, isotopic evidence can be more persuasive than other approaches because it is so quantitatively sensitive, typically requiring samples of less than 0.1 to only a few milligrams of material to be delivered to the mass spectrometer, with high quantitative resolution in the ability to distinguish between materials with different origins and production histories.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that instances of fraud might be directly detectable from analytical "fingerprints" which could demonstrate sameness or differences between samples. [1][2][3] Consequently, recent initiatives have been directed toward an evaluation of computer-based methods that could be used to distinguish within-and between-batch product consistency, to examine the effects of process changes in the production of pharmaceutical products, and to determine whether a product marketed today is the same as that which was originally approved. 1 It is well-established that information on the microscopic chemical composition of products provided by chromatographic trace organic impurity patterns represents an important component of the product fingerprint.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of fraudulent practices at a generic pharmaceutical firm in 1989 led the U.S. Food and Drug Administration (FDA) to conduct large-scale investigations into the pharmaceutical industry. It has been suggested that instances of fraud might be directly detectable from analytical “fingerprints” which could demonstrate sameness or differences between samples. Consequently, recent initiatives have been directed toward an evaluation of computer-based methods that could be used to distinguish within- and between-batch product consistency, to examine the effects of process changes in the production of pharmaceutical products, and to determine whether a product marketed today is the same as that which was originally approved…”
Section: Introductionmentioning
confidence: 99%